Porous structure suitable for hydro-fluctuation belt bank slope and manufacturing method thereof

By using porous structures made of volcanic stone, gelling materials and water reducing agents, the wave removal and filtration performance of the bank slope of the desolation zone is improved, and the problems of erosion and soil erosion caused by waves are solved, and effective protection and ecological restoration of the bank slope are achieved.

CN119528517APending Publication Date: 2025-02-28TIANFU YONGXING LAB +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411780152.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the problems of bank slope erosion and soil erosion in the desolation zone caused by waves.

Method used

The porous structure consisting of volcanic stone, gelling materials and water reducing agent is adopted to enhance its resistance to hydraulic erosion by improving its wave removal and filtration performance.

Benefits of technology

This porous structure has high compressive strength and good water permeability, which can effectively prevent erosion and soil erosion of the bank slope, and is suitable for ecological restoration of the bank slope in the desolation zone.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention discloses a porous structure suitable for a hydro-fluctuation belt bank slope and a manufacturing method of the porous structure, belongs to the technical field of ecological restoration of hydro-fluctuation belts, and aims to solve the problems of erosion of the hydro-fluctuation belt bank slope and water and soil loss caused by waves. The porous structure suitable for the hydro-fluctuation belt bank slope is prepared from the following raw materials in percentage by weight: 64.1-68.2% of pelelith; 31.5%-35.6% of a cementing material; and 0.1-0.6% of a water reducing agent. The manufacturing method comprises the following steps: pouring all pelelith into a stirrer, pouring part of water, and stirring to pre-wet the pelelith; adding part of the cementing material and the water reducing agent into the stirrer, and stirring; adding the rest of water into the stirrer, and continuously stirring to thin the shell and uniformly wrap the shell; slowly adding the rest of the cementing material and the water reducing agent into the stirrer, and stirring while adding; and after stirring is finished, pouring into a mold, vibrating and forming to obtain a porous structure. The porous structure has high strength, enough vegetation space and good water permeability, and is very suitable for the bank slope of the hydro-fluctuation belt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ecological restoration of a drawdown zone, and relates to a porous structure used in ecological restoration of a drawdown zone, and in particular to a porous structure with wave-breaking and anti-filtration performance suitable for a bank slope of a drawdown zone, and a manufacturing method thereof. Background Art

[0002] There are many lakes, rivers and reservoirs in my country, all of which have natural or artificial water level regulation. Based on water level regulation, the water level rises and falls periodically, forming a drawdown zone on the river bank slope. The drawdown zone refers to the area between the highest water level and the lowest water level formed due to periodic water storage caused by natural or artificial regulation. The drawdown zone is a special riverbank zone, which belongs to the transition area between land and water, and is a typical ecological transition zone.

[0003] As the water level rises and falls periodically between the highest water level and the lowest water level, the geological conditions and ecological environment in the drawdown zone have undergone tremendous changes, which has also brought about a series of problems.

[0004] In view of the problems caused by the above-mentioned drawdown belt, more and more people are paying attention to the repair and reconstruction of the drawdown belt, especially the protection of the bank slope of the drawdown belt. For the protection of the bank slope of the drawdown belt, the existing technology mainly involves setting up slope protection structures on the bank slope and planting vegetation.

[0005] The invention patent with application number 202210943517.9 discloses a method for ecological restoration of the drawdown zone of a reservoir, which includes: drawing the boundary line of the drawdown zone, determining the area of ​​the drawdown zone, and prefabricating a vegetation maintenance structure of the drawdown zone. The vegetation maintenance structure of the drawdown zone includes a water storage device and a ventilation device. The water storage device is set from the top boundary line of the drawdown zone to the bottom boundary line of the drawdown zone, and the ventilation device is set from the bottom boundary line of the drawdown zone to the top boundary line of the drawdown zone. The drawdown zone area is divided into two halves, and waterlogging and drought-resistant plants are planted in the vegetation maintenance structure of the drawdown zone. During the flood season, the plants are not easily flooded and rotten; during the dry season, the plants will not wither and die; in addition, the upstream water diversion control is used to use the upstream water for plant irrigation to prevent the plants from withering during the dry season.

[0006] The invention patent with application number 202311152208.0 discloses a vegetation restoration device suitable for the drawdown zone of a reservoir, including a planting chain belt, which is a pumice unit connected in sequence by connecting parts, and the pumice unit includes a bowl-shaped pumice with an opening facing upward; its production method includes the steps of sintering, slurry making, spraying, drilling, and serial connection; its application uses a planting chain belt to be fixed at one end to the shore in the flood season; the device uses artificial pumice to construct a planting chain belt, and the flood season It floats on water during the dry season and hangs on the cliff or steep slope during the dry season; the weight ratio and connection relationship are set to keep the opening of the bowl-shaped pumice facing upward, avoid plant lodging during the dry season, and make the overall landscape natural and beautiful; multiple pumice units are easy to maintain and reasonably increase the greening restoration area; lightweight metal frames clamp pumice blocks to increase buoyancy and increase strength to resist pulling; seeds are sown directly with mud, without a seedling growth period, and have a high survival rate; the porous structure of the bowl-shaped pumice is conducive to rooting and stem consolidation, inhibits the growth of algae, and has good air permeability for root growth.

[0007] In addition, the invention patent with application number 202311152212.7 discloses a slope protection device for a drawdown zone, including a planting trough, the surface of which is attached with a slurry containing plant seeds, and the planting trough is a porous structure with a bulk density of 1 to 1.1; its production method includes the steps of prefabrication, slurry preparation, slurry soaking, drying, etc.; the device uses a porous structure with a small bulk density to attach the slurry containing plant seeds, which reduces the filling of the medium, is light in weight, free of pulling, and has a low risk of falling off; the multi-pores are conducive to the fixed growth of microorganisms and the firmness of plant roots, and the slurry stabilizes the plant seeds thereon, improves the utilization rate of fertilizer, inhibits water evaporation, enhances water holding capacity, reduces soil erosion, improves strength, and is not easy to weather; the germination of plants adapts to the environment, there is no slow seedling period, and the emergence rate is high; the bottom depression can disperse the water pressure, intercept aquatic plants, epiphytic algae and ground plants, provide a place for organisms, intercept mud and sand to cover the rock slope; the wave-breaking blocks improve the structural strength and buffer the impact and resistance of waves.

[0008] For example, the protection or repair device of the drawdown zone in the above-mentioned invention patent can effectively prevent the erosion of the bank slope, soil erosion, etc. through the device and the vegetation planted on the device. However, waves are also an important factor causing the erosion of the bank slope and soil erosion, and the devices in the above-mentioned invention patents cannot effectively solve the problem of erosion of the bank slope and soil erosion caused by waves. Summary of the invention

[0009] The purpose of the present invention is to solve the problem of bank erosion and soil loss caused by waves in a drawdown zone, provide a porous structure suitable for the bank of a drawdown zone and a method for making the same, and improve the ability of the bank of the drawdown zone to resist hydraulic erosion by improving the wave-breaking and anti-filtration performance of the porous structure.

[0010] In order to achieve the above-mentioned purpose, the present invention specifically adopts the following technical solutions: A porous structure suitable for a bank slope of a drawdown zone, made of raw materials containing the following weight percentages: Volcanic rocks 64.1-68.2%; Cementitious materials 31.5~35.6%; Water reducing agent 0.1~0.6%.

[0011] Furthermore, the aggregate size of the volcanic rock is 16~31.5mm and the apparent density is 1632.5~1720.3kg / m 3 , bulk density is 682.9~761.7 kg / m 3 , the void ratio is 0.56~0.58%, and the water absorption rate of aggregate is 7.6~7.8%.

[0012] Further, the gelling material is made of raw materials comprising the following weight percentages: Portland cement 50.2~54.1%; Fly ash 10.1~14.5%; Water 32.3~37.9%.

[0013] Further, the silicate cement is silicate cement with a strength grade of P.O42.5, and the fly ash is secondary fly ash; Among them, the loss on ignition of silicate cement is 0.97, and the weight percentage of each oxide in silicate cement is: SiO220.38~22.35%; Fe2O34.47~4.82%; Al2O35.23~5.89%; CaO61.01~63.19%; MgO2.05~2.96%; SO31.55~1.73%; NaO1.02~1.10%.

[0014] Furthermore, the initial setting time of silicate cement is 70~110min, the final setting time is 150~180min, the 3-day flexural strength is 6.41~6.92Mpa, the 28-day flexural strength is 8.48~8.83Mpa, the 3-day compressive strength is 27.23~30.27Mpa, and the 28-day compressive strength is 53.90~56.61Mpa.

[0015] Furthermore, the bulk density of the water reducing agent is 600±100 kg / m 3 , pH value is 8±1.0, and water content is ≤3.

[0016] Furthermore, in the porous structure, the ash-to-water ratio is 0.377 and the weight percentage of the cementitious material is 32.7%.

[0017] A method for making a porous structure suitable for a bank slope of a drawdown zone, the specific steps are: (1) Pour all the volcanic rocks into a mixer, add 45-55% water, and stir to pre-wet the volcanic rocks; (2) Add 60-80% of cementitious material and 60-80% of water reducing agent into the mixer and stir until the volcanic rock is completely covered by the adhesive material to form a shell; (3) Add the remaining water to the blender and continue blending until the shell becomes thinner and the coating is evenly distributed. (4) Slowly add the remaining gelling material and water reducing agent into the mixer while stirring; (5) After the mixing is completed, the mixed material is poured into a mold and vibrated, and then molded to obtain a porous structure.

[0018] Furthermore, the stirring time in step (1) to step (4) is 1-2 min, 2-3 min, 2-3 min, and 1-2 min, respectively.

[0019] The beneficial effects of the present invention are as follows: In the present invention, the porous structure includes lightweight aggregate volcanic rock, cementitious material, water reducer and water, and is prepared by a shell-making method. During the stirring process, the amount of cementitious material added is relatively small, and the aggregates are mainly in a chain state, so that it has excellent pore structure and vegetation performance; after testing, the surface of the aggregate is wrapped with a uniform porous structure, the 7-day compressive strength can be as high as 0.95Mpa, the 28-day compressive strength can be as high as 1.34Mpa, and the overall compressive stability is relatively high; the total porosity per unit cubic volume in the porous structure can be as high as 45%, and the effective porosity can be as high as 40%. The porous structure has high strength and sufficient vegetation space and good water permeability, and is very suitable for the bank slope of the drawdown zone, and can effectively solve the problems of bank slope erosion and soil erosion in the drawdown zone caused by waves. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a schematic diagram of a porous structure in an interlocking state in the present invention; Figure 2 It is a schematic diagram of the result of the compression test of the present invention; Among them, Figure A shows the compressive strength under different water-cement ratios, Figure B shows the compressive strength under different aggregate particle sizes, and Figure C shows the compressive strength under different cementitious material dosages; Figure 3 is a schematic diagram of the results of the pore characteristics test of the present invention; Among them, Figure A shows the porosity change under different water-cement ratios, Figure B shows the porosity change under different aggregate particle sizes, and Figure C shows the porosity change under different cementitious material dosages; Figure 4 Schematic diagram of the relationship between effective porosity and total porosity in the present invention; Figure 5 It is a schematic diagram of the result of the water permeability test of the present invention; Among them, Figure A shows the change of water permeability coefficient under different water-cement ratios, Figure B shows the change of water permeability coefficient under different aggregate particle sizes, and Figure C shows the change of water permeability coefficient under different cementitious material dosages; Figure 6 It is a schematic diagram of the relationship between effective porosity and water permeability in the present invention. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.

[0022] Therefore, based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative work shall fall within the scope of protection of the present invention.

[0023] Example 1 This embodiment provides a porous structure suitable for a bank slope of a drawdown zone, which is made of raw materials containing the following weight percentages: volcanic rock 64.5%; Cementitious materials 35%; Water reducing agent 0.5%.

[0024] The aggregate size of the volcanic rock is 18 mm and the apparent density is 1642.6 kg / m 3 , bulk density is 691.7 kg / m 3 , the void ratio is 0.56% and the aggregate water absorption rate is 7.6%.

[0025] The gelling material is made of raw materials containing the following weight percentages: Portland cement 53.2%; Fly ash 10.5%; Water 36.3%.

[0026] Among them, the silicate cement is silicate cement with a strength grade of P.O42.5, and the fly ash is secondary fly ash; the loss on ignition of the silicate cement is 0.97, and the weight percentage of each oxide in the silicate cement is: SiO2 21.63%; Fe2O34.71%; Al2O35.84%; CaO 63.02%; MgO2.13%; SO31.59%; NaO1.08%.

[0027] The initial setting time of silicate cement is 75 minutes, the final setting time is 154 minutes, the flexural strength at 3 days is 6.45 MPa, the flexural strength at 28 days is 8.53 MPa, the compressive strength at 3 days is 27.82 MPa, and the compressive strength at 28 days is 54.21 MPa.

[0028] The bulk density of the water reducer is 526 kg / m 3 , pH value is 7.3, and water content is 2.3.

[0029] The gray-water ratio is 0.377.

[0030] This embodiment also provides a method for making the porous structure, the specific steps are: (1) Pour all the volcanic rocks into a mixer and add 46% water (the water here is not the water in the volcanic rocks, cementitious materials, and water reducers mentioned above; the amount of water here can be selected according to actual conditions, the same below), and stir for 1 minute to pre-wet the volcanic rocks; (2) Add 62% of cementitious material and 65% of water reducing agent into the mixer and stir for 3 minutes until the volcanic rock is completely wrapped by the adhesive material to form a shell; (3) Add the remaining water to the blender and continue blending for 2 minutes to make the shell thinner and more evenly coated. (4) Slowly add the remaining gelling material and water reducing agent into the mixer, stirring for 2 minutes; (5) After the mixing is completed, the mixed material is poured into a mold and vibrated, and then molded to obtain a porous structure.

[0031] Example 2 This embodiment provides a porous structure suitable for a bank slope of a drawdown zone, which is made of raw materials containing the following weight percentages: volcanic rock 64.9%; cementitious materials 34.8%; Water reducing agent 0.3%.

[0032] The aggregate size of the volcanic rock is 22.3 mm and the apparent density is 1659.4 kg / m 3 , bulk density is 706.4kg / m 3, the void ratio is 0.56% and the aggregate water absorption rate is 7.6%.

[0033] The gelling material is made of raw materials containing the following weight percentages: Portland cement 53.3%; Fly ash 12.3%; Water 34.4%.

[0034] Among them, the silicate cement is silicate cement with a strength grade of P.O42.5, and the fly ash is secondary fly ash; the loss on ignition of the silicate cement is 0.97, and the weight percentage of each oxide in the silicate cement is: SiO2 21.59%; Fe2O34.61%; Al2O35.37%; CaO 62.84%; MgO2.84%; SO31.70%; NaO1.05%.

[0035] The initial setting time of silicate cement is 103min, the final setting time is 172min, the flexural strength at 3 days is 6.53Mpa, the flexural strength at 28 days is 8.64Mpa, the compressive strength at 3 days is 28.94Mpa, and the compressive strength at 28 days is 56.21Mpa.

[0036] The bulk density of the water reducer is 567 kg / m 3 , pH value is 7.5, and water content is 1.8.

[0037] The gray-water ratio is 0.317.

[0038] This embodiment also provides a method for making the porous structure, the specific steps are: (1) Pour all the volcanic rocks into a blender and add 52% water. Stir for 2 minutes to pre-wet the volcanic rocks. (2) Add 75% of cementitious material and 62% of water reducing agent into the mixer and stir for 2 minutes until the volcanic rock is completely wrapped by the adhesive material to form a shell; (3) Add the remaining water to the blender and continue blending for 3 minutes until the outer shell becomes thinner and the coating is evenly distributed. (4) Slowly add the remaining gelling material and water reducing agent into the mixer, stirring while adding for 1 minute; (5) After the mixing is completed, the mixed material is poured into a mold and vibrated, and then molded to obtain a porous structure.

[0039] Example 3 This embodiment provides a porous structure suitable for a bank slope of a drawdown zone, which is made of raw materials containing the following weight percentages: volcanic rock 66.9%; cementitious materials 32.9%; Water reducing agent 0.2%.

[0040] The aggregate size of the volcanic rock is 30.4 mm and the apparent density is 1702.4 kg / m 3 , bulk density is 742.4 kg / m 3 , the void ratio is 0.57% and the aggregate water absorption rate is 7.7%.

[0041] The gelling material is made of raw materials containing the following weight percentages: Portland cement 52.2%; Fly ash 14.1%; Water 33.7%.

[0042] Among them, the silicate cement is silicate cement with a strength grade of P.O42.5, and the fly ash is secondary fly ash; the loss on ignition of the silicate cement is 0.97, and the weight percentage of each oxide in the silicate cement is: SiO2 22.17%; Fe2O34.75%; Al2O35.76%; CaO 61.78%; MgO2.82%; SO31.64%; NaO1.08%.

[0043] The initial setting time of silicate cement is 89 minutes, the final setting time is 158 minutes, the flexural strength at 3 days is 6.81 MPa, the flexural strength at 28 days is 8.73 MPa, the compressive strength at 3 days is 29.24 MPa, and the compressive strength at 28 days is 55.42 MPa.

[0044] The bulk density of the water reducer is 672 kg / m 3 , pH value is 8.5, and water content is 2.4.

[0045] The gray-water ratio is 0.364.

[0046] This embodiment also provides a method for making the porous structure, the specific steps are: (1) Pour all the volcanic rocks into a blender and add 49% water. Stir for 2 minutes to pre-wet the volcanic rocks. (2) Add 67% of cementitious material and 76% of water reducing agent into the mixer and stir for 3 minutes until the volcanic rock is completely wrapped by the adhesive material to form a shell; (3) Add the remaining water to the blender and continue blending for 3 minutes until the outer shell becomes thinner and the coating is evenly distributed. (4) Slowly add the remaining gelling material and water reducing agent into the mixer, stirring for 2 minutes; (5) After the mixing is completed, the mixed material is poured into a mold and vibrated, and then molded to obtain a porous structure.

[0047] Example 4 This embodiment provides a porous structure suitable for a bank slope of a drawdown zone, which is made of raw materials containing the following weight percentages: volcanic rock 65.9%; cementitious materials 33.7%; Water reducing agent 0.4%.

[0048] The aggregate size of the volcanic rock is 27.4 mm and the apparent density is 1652.7 kg / m 3 , bulk density is 724.5kg / m 3 , the void ratio is 0.58% and the aggregate water absorption rate is 7.8%.

[0049] The gelling material is made of raw materials containing the following weight percentages: Portland cement 51.9%; Fly ash 11.7%; Water 36.4%.

[0050] Among them, the silicate cement is silicate cement with a strength grade of P.O42.5, and the fly ash is secondary fly ash; the loss on ignition of the silicate cement is 0.97, and the weight percentage of each oxide in the silicate cement is: SiO2 22.27%; Fe2O34.52%; Al2O35.49%; CaO 62.53%; MgO2.58%; SO31.58%; NaO1.03%.

[0051] The initial setting time of silicate cement is 96 minutes, the final setting time is 164 minutes, the flexural strength at 3 days is 6.78 MPa, the flexural strength at 28 days is 8.81 MPa, the compressive strength at 3 days is 28.61 MPa, and the compressive strength at 28 days is 53.99 MPa.

[0052] The bulk density of the water reducer is 649 kg / m 3 , pH value is 8.2, and water content is 2.8.

[0053] The gray-water ratio is 0.355.

[0054] This embodiment also provides a method for making the porous structure, the specific steps are: (1) Pour all the volcanic rocks into a blender and add 53% water. Stir for 1 to 2 minutes to pre-wet the volcanic rocks. (2) Add 75% of cementitious material and 72% of water reducing agent into the mixer and stir for 3 minutes until the volcanic rock is completely wrapped by the adhesive material to form a shell; (3) Add the remaining water to the blender and continue blending for 2 minutes to make the shell thinner and more evenly coated. (4) Slowly add the remaining gelling material and water reducing agent into the mixer, stirring while adding for 1 minute; (5) After the mixing is completed, the mixed material is poured into a mold and vibrated, and then molded to obtain a porous structure.

[0055] Test example (compressive strength) A small mixer was used to prepare multiple groups of porous structures with a size of 100mm*100mm*100mm. The multiple groups of porous structures can be divided into porous structure combinations with different water-cement ratios, porous structure combinations with different aggregate particle sizes, and porous structure combinations with different cementitious material dosages. The above-mentioned porous structures were molded and demoulded within 24 hours to obtain test pieces. The test pieces were immersed in water and cured to the corresponding age before the compression test. The compressive strength test method was referred to the "Standard for Test Methods of Mechanical Properties of Ordinary Concrete". The tester was a microcomputer-controlled electro-hydraulic servo pressure testing machine, model: YAW-600D.

[0056] The specific steps of the test are: (1) After the specimens have been cured for 28 days, the compressive surface is sealed with M5 mortar to ensure that the compressive surface is flat. The compressive strength test is carried out 2 days after the sealing treatment. (2) Align the smooth surface of the specimen with the upper and lower pressure plates of the compression machine. After the center is symmetrical, operate the compression machine to lift and lower so that the upper and lower pressure plates are in uniform contact with the specimen; (3) Turn on the compression machine and load at a loading rate of 0.1 MPa / s until the specimen is damaged, then stop loading.

[0057] Calculate the compressive strength of the specimen using the following formula:

[0058] In the formula, Indicates the compressive strength of standard cubic specimen (MPa), represents the specimen failure load (N), Indicates the compressive area of ​​the specimen (mm 2 ).

[0059] Test results: like Figure 2 As shown in A, the compressive strength of the porous structure gradually increases with the extension of the curing age. Under the same curing age, when the water-cement ratio increases from 0.25 to 0.35, the compressive strength gradually increases. When the water-cement ratio is 0.35, the 28-day compressive strength reaches a maximum value of 1.1 MPa. When the water-cement ratio continues to increase, the compressive strength decreases instead. According to research, this is mainly because when the water-cement ratio is small, the slurry wraps the aggregate unevenly and the slurry is dry, resulting in incomplete hydration; when the water-cement ratio is 0.35, the aggregate surface is uniformly wrapped with a porous structure with high overall stability, while when the water-cement ratio is greater than 0.35, the slurry is too thin and the fluidity is high, resulting in a thinner thickness of the aggregate wrapping, and the slurry will be deposited at the bottom of the test block due to its own gravity, resulting in a thicker thickness at the bottom and thinner thickness at the top, and the overall compressive strength of the test block is reduced. Therefore, a water-cement ratio of about 0.35 is more suitable.

[0060] like Figure 2 As shown in Figure B, at a fixed water-cement ratio (0.35) and a fixed unit cementitious slurry volume (20%), the smaller the aggregate size, the higher the compressive strength of the porous component. This is because when the aggregate size is smaller, there will be more contact points between the coarse aggregates, the porous structure will be closer to solid, the pores will be fine, and the vegetation slurry will be difficult to penetrate. Considering the two factors of compressive strength and vegetation slurry penetration, it is considered that the selection of aggregates of about 2 cm is more appropriate.

[0061] like Figure 2 As shown in C, with the increase of gelled slurry, the compressive strength of the porous skeleton increases, but too much slurry will cause the slurry to sink, resulting in the upper and lower sides of the skeleton being disconnected and the water permeability being poor.

[0062] Test example (pore characteristics) The porous structure is a porous structure composed of volcanic rocks, cementitious materials and water reducing agents. Different from ordinary concrete structures, it has large pores and good connectivity. The pore characteristics are closely related to the permeability of the porous structure, vegetation space and other functions.

[0063] The specific steps of the test are: (1) Soak the sample in water and keep it cured until it is saturated with water. Take it out 1 day in advance and put it on a hydrostatic balance to weigh the mass m1.

[0064] (2) Then place it in air for 24 hours and weigh it, the natural mass is m2.

[0065] (3) On the day of aging, place the sample in a drying oven (60℃, 24h), dry it to constant weight, and weigh its mass m3.

[0066] The total porosity calculation formula is:

[0067] The calculation formula of connected porosity is:

[0068] In the formula, Indicates the density of water (g / cm 3 ), Indicates the volume of water discharged (cm 3 ), represents the mass in water (g), Indicates natural weight (g), Indicates the oven-dried constant weight (g).

[0069] Test results: like Figure 3 As shown in the figure, in the single factor test of water-cement ratio and aggregate particle size, there is no significant difference in porosity and effective porosity between different water-cement ratios and different aggregate particle sizes. The total porosity is in the range of 40.2-45.3%, and the effective porosity is about 35.6-39.5%, with a difference of about 6%, indicating that there are about 6% closed pores in the porous structure, which cannot be used for subsequent plant growth and are invalid pores.

[0070] At different cementitious volume dosages, the porosity of the two parts varies greatly, indicating that the cementitious slurry dosage is the most critical influencing factor controlling the porosity of the porous structure. With the increase of cementitious slurry dosage, the porosity and effective porosity of the porous structure per unit volume are significantly reduced. The total porosity decreases from 46.3% to 33.1%, while the effective porosity decreases from 41.3% to 26.8%. Both porosities are higher than the theoretically calculated porosity. This is because there is a certain amount of slurry loss in the process of making the porous structure, and the loss is about 5~7%.

[0071] like Figure 4 As shown in the figure, the porosity and effective porosity of the porous structure prepared by the single factor test under different water-cement ratios, aggregate particle sizes, and cementitious paste dosages were measured. According to the previous test results, the porosity and effective porosity of the porous structure were statistically analyzed, and it was found that there was a good quadratic function relationship between the two, R 2 =0.9183.

[0072] Test example (water permeability coefficient) The water permeability coefficient is an indicator to measure the water permeability of porous structures. The porous structure has continuous voids and semi-continuous voids inside, which has good water permeability. The porous structure has coarse aggregates and good drainage capacity. This test example uses a laboratory-made constant head instrument to measure the water permeability coefficient of its test block in accordance with "Water Permeability of Macroporous Concrete and Its Determination Method".

[0073] Test method: (1) Cylindrical (110 mm in diameter, 150 mm in height) porous structures with different mix ratio designs were prepared and placed in water for curing for 28 days. The specimens were then immersed in water for 24 hours to achieve saturation. (2) Place the specimens that have reached the required age into a PVC pipe, open the water supply valve to allow water to enter the container, and adjust the water inlet to keep a certain water level (about 150 mm) in the prism sealing device. After the amount of water flowing out of the overflow port of the prism sealing device stabilizes, use a measuring container to collect water from the outlet and record the amount of water flowing out in 90 s (Q). Measure three times and take the average value.

[0074] (3) Use a steel ruler to measure the difference (H) between the water level in the prism seal and the water level on the upper surface of the test piece, accurate to 1 mm. Use a thermometer to measure the temperature of the water in the prism seal during the test (T), accurate to 1°C.

[0075] The formula for calculating the water permeability coefficient is:

[0076] in, Indicates the water permeability coefficient of the test piece at water temperature T℃ (mm / s), Indicates the amount of water flowing out in t seconds (mm 3 ), Indicates the thickness of the specimen (mm 2 ), Indicates the upper surface area (mm 2 ), Indicates the water level difference (s).

[0077] The test result is based on the average value of the three test pieces, and the calculation is accurate to 1.0*10 -2 mm / s.

[0078] This test example uses 15℃ water temperature as the standard temperature. The water permeability coefficient at the standard temperature should be calculated according to the formula:

[0079] in, Indicates the water permeability coefficient of the specimen at standard temperature (mm / s), Indicates the dynamic viscosity of water at T℃ (kPa·s), Indicates the dynamic viscosity of water at 15°C (kPa·s), Represents the dynamic viscosity ratio of water.

[0080] Test results: like Figure 5 As shown in the figure, as the water-cement ratio increases, the water permeability coefficient increases slightly. This is because as the water-cement ratio increases, the fluidity of the slurry increases, which leads to a thinner wrapping thickness of the slurry on the aggregate and an increase in the permeable area per unit thickness. For different aggregate particle sizes, the water permeability coefficient is positively correlated with the particle size. When the aggregate increases, the pores formed by the accumulation are also larger, so the water permeability coefficient also increases accordingly. As for the effect of the cementitious slurry dosage on the water permeability coefficient, it can be seen that as the cementitious slurry in the unit volume structure increases, the water permeability coefficient decreases significantly. When the slurry volume dosage is 15~25%, the water permeability coefficient ranges from 2.56~3.55 cm / s. When the dosage is 30%, the water permeability coefficient is 0.03 cm / s, and the bottom of the porous structure is sealed by sedimentation. At this time, the porous structure has lost its permeability. In summary, the volume dosage of cementitious slurry should be below 25%.

[0081] like Figure 6 As shown in Figure 2, when the cementitious content is less than 25%, the effective porosity and water permeability coefficient show a strong correlation, and the correlation coefficient R 2 As high as 0.9461. It can be seen that the water permeability coefficient gradually increases with the increase of effective porosity, that is, the effective porosity is particularly important for the water permeability of porous structures. Therefore, when preparing porous structures, it is particularly important to choose the appropriate amount of cementitious slurry. Combined with the above porosity research, in order to make the porous structure have enough vegetation space and good water permeability, the volume content of cementitious slurry should be controlled below 25%, which is consistent with the previous conclusion.

Claims

1. A porous structure suitable for a bank slope of a drawdown zone, characterized in that: Made from the following raw materials in weight percentage: Volcanic rocks 64.1-68.2%; Cementitious materials 31.5~35.6%; Water reducing agent 0.1~0.6%.

2. A porous structure suitable for a bank slope of a drawdown zone as claimed in claim 1, characterized in that: The aggregate size of volcanic rock is 16~31.5mm, and the apparent density is 1632.5~1720.3kg / m 3 , bulk density is 682.9~761.7 kg / m 3 , the void ratio is 0.56~0.58%, and the water absorption rate of aggregate is 7.6~7.8%.

3. A porous structure suitable for a bank slope of a drawdown zone as claimed in claim 1, characterized in that: The cementitious material is made of raw materials containing the following weight percentages: Portland cement 50.2~54.1%; Fly ash 10.1~14.5%; Water 32.3~37.9%.

4. A porous structure suitable for a bank slope of a drawdown zone as claimed in claim 3, characterized in that: The silicate cement is silicate cement with a strength grade of P.O42.5, and the fly ash is secondary fly ash; Among them, the loss on ignition of silicate cement is 0.97, and the weight percentage of each oxide in silicate cement is: SiO220.38~22.35%; Fe2O34.47~4.82%; Al2O35.23~5.89%; CaO61.01~63.19%; MgO2.05~2.96%; SO31.55~1.73%; NaO1.02~1.10%.

5. The porous structure suitable for the bank slope of the drawdown zone as claimed in claim 3, characterized in that: The initial setting time of silicate cement is 70~110min, the final setting time is 150~180min, the flexural strength at 3 days is 6.41~6.92Mpa, the flexural strength at 28 days is 8.48~8.83Mpa, the compressive strength at 3 days is 27.23~30.27Mpa, and the compressive strength at 28 days is 53.90~56.61Mpa.

6. The porous structure suitable for the bank slope of the drawdown zone according to claim 1, characterized in that: The bulk density of the water reducing agent is 600±100 kg / m 3 , pH value is 8±1.0, and water content is ≤3.

7. The porous structure suitable for the bank slope of the drawdown zone according to claim 1, characterized in that: In the porous structure, the ash-water ratio is 0.377 and the weight percentage of cementitious materials is 32.7%.

8. A method for manufacturing a porous structure suitable for a bank slope of a drawdown zone according to any one of claims 1 to 7, characterized in that: The specific steps are: (1) Pour all the volcanic rocks into a mixer, add 45-55% water, and stir to pre-wet the volcanic rocks; (2) Add 60-80% of cementitious material and 60-80% of water reducing agent into the mixer and stir until the volcanic rock is completely covered by the adhesive material to form a shell; (3) Add the remaining water to the blender and continue blending until the shell becomes thinner and the coating is evenly distributed. (4) Slowly add the remaining gelling material and water reducing agent into the mixer while stirring; (5) After the mixing is completed, the mixed material is poured into a mold and vibrated, and then molded to obtain a porous structure.

9. The method of claim 8, wherein: The stirring time in step (1) to step (4) is: 1~2min, 2~3min, 2~3min, 1~2min, respectively.

Citation Information

Patent Citations

  • Ecological restoration method for water-level-fluctuating zone of reservoir

    CN115262469A

  • Vegetation restoration device suitable for hydro-fluctuation belt of reservoir and production method of vegetation restoration device

    CN117099586A

  • Hydro-fluctuation belt slope protection device and production method thereof

    CN117356310A